Global political Islam - Mandaville, Peter G. 1971- (Routledge, 2007)
This book is an accessible and comprehensive account of the international and global dimensions of political Islam in the twenty-first century. Drawing on insights from international relations and Islamic studies, it explains the complex interaction between political Islam, nationalism and globalisation and demonstrates how this transcends any simplified model of a 'clash of civilizations'. The book illuminates the theory with a number of detailed case studies of the Arab Middle East, Central & South Asia, Southeast Asia and Islam in Europe and North America. It also provides a detailed account of Al-Qaeda as a transnational network. Subjects covered by the book include: history of political Islam, how political Islam interacts with the nation state and the global economy, the cultural and identity politics of Islam, a wide variety of international case studies, and profiles of key movements and individuals. Fully illustrated throughout, featuring maps, a glossary and suggestions for further reading, this is the ideal introduction to the crucial role of political Islam in the contemporary world.